Perceraian ; Sebuah Tinjauan di Masa Pandemi Covid-19 - Kadir, Andi Risal; Amir, Irfan (IAIN Bone, 2022)
The purpose of this study was to determine the divorce rate during the Covid-19 pandemic in Kolaka Regency between 2019-2021 at the Kolaka Religious Court and what factors caused the COVID-19 pandemic at the Kolaka Religious Court. The results obtained fromthis study are divorce during the covid 19 pandemic in Kolaka Regency increased by 58 cases, divorce increased related to the covid 19 pandemic, as for the factors that caused divorce during the covid 19 pandemic, namely the moral crisis factor, forced marriage factor, the responsibility factor, the domestic violence factor, the prison sentence factor, the household disharmony factor, the apostate factor and the economic factor, while the main factor in the occurrence of divorce during the pandemic at the Kolaka Religious Court was due to economic factors.